From Industrial Relations to the Employment Relationship: The Development of Research in Britain - Edwards, P.K. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1995)
This paper uses certification data from the province of Nova Scotia to provide further evidence that convergence of industrial relations Systems between the U.S. and Canada is far from unavoidable. Contrary to arguments advanced by Troy, private sector organizing in Canada, even when operating under a U.S.-style legal environment, remains remarkably robust, posting a win rate of 68 percent over a ten-year period with no evidence of longitudinal decline. Furthermore, there is compelling evidence that international unions are unable to match the organizing performance of their Canadian counterparts.